2009
DOI: 10.4049/jimmunol.0804191
|View full text |Cite
|
Sign up to set email alerts
|

IgM Antibodies to Apoptosis-Associated Determinants Recruit C1q and Enhance Dendritic Cell Phagocytosis of Apoptotic Cells

Abstract: Natural Abs, which arise without known immune exposure, have been described that specifically recognize cells dying from apoptosis, but their role in innate immunity remains poorly understood. Herein, we show that the immune response to neoantigenic determinants on apoptotic thymocytes is dominated by Abs to oxidation-associated Ags, phosphorylcholine (PC), a head group that becomes exposed during programmed cell death, and malondialdehyde (MDA), a reactive aldehyde degradation product of polyunsaturated lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
250
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 203 publications
(263 citation statements)
references
References 72 publications
(85 reference statements)
10
250
0
3
Order By: Relevance
“…C1q has been shown to interact with apoptotic cells both directly (7), which is the subject of this study, and indirectly via C-reactive protein (34), serum amyloid P, pentraxin 3 (35), and natural IgM (36). DNA has long been known as a ligand for C1q and here we further characterized the interaction by determining the K D value using surface plasmon resonance, confirming a very strong interaction.…”
Section: Discussionsupporting
confidence: 68%
“…C1q has been shown to interact with apoptotic cells both directly (7), which is the subject of this study, and indirectly via C-reactive protein (34), serum amyloid P, pentraxin 3 (35), and natural IgM (36). DNA has long been known as a ligand for C1q and here we further characterized the interaction by determining the K D value using surface plasmon resonance, confirming a very strong interaction.…”
Section: Discussionsupporting
confidence: 68%
“…The realization that the classic PC-reactive T15 clone recognizes oxidation specific epitopes (1) has opened up a whole new aspect of investigation. Subsequent research has demonstrated that anti-PC aids in clearance of apoptotic cells (6,30) and prevents the formation of pathogenic foam cells in atherosclerosis by clearing oxidized low density lipoprotein (1). Murine studies with PC vaccination have shown strong beneficial effects on experimental atherosclerosis in vivo (11)(12)(13), and human epidemiology has consistently linked anti-PC insufficiency to cardiovascular events (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lymphocytes treated with chagasic IgM failed to reduce parasite load, and did not elicit TNF-a production by macrophages (not shown). IgM mediates clearance through deposition of C1q and iC3b on apoptotic cells [16,30,31]. Opsonization by C1q or iC3b leads to silent, non-inflammatory removal of dead cells [32][33][34].…”
Section: Discussionmentioning
confidence: 99%